Zinc Oxide Nanomaterials: Toxicity Mechanism and Biomedical Applications - Maryam Akhwater (African Journal of Advanced Pure and Applied Sciences, 2024)
Over the last several decades, nanostructured materials have been the focus of intense research, due to their remarkable characteristics suitable for exploitation in electronics, optical, electrochemical, electromechanical and photonics applications. In particular, zinc oxide nanostructures (ZnO-NSs) have been extensively utilized as an efficient intracellular platform to introduce different biomolecules into various types of cells due to their minimal diameter size with a high aspect ratio. Importantly, comprehension of the extraordinary functional properties of ZnO nanomaterials and their promising applications as an elementary unit of future nanodevices is the focus of the current research activities. This work is dedicated to reviewing the outstanding properties of several nanostructured ZnO materials and their functionality in different biomedical and healthcare applications. The potential feasibility of ZnO nanomaterial is further highlighted through its integration with different antibacterial, anticancer, tissue engineering, wound healing, and bioimaging applications as well as potential biomolecule and drug delivery platforms.